2004
DOI: 10.1063/1.1650893
|View full text |Cite
|
Sign up to set email alerts
|

Electric field effect on the rhombohedral–rhombohedral phase transformation in tin modified lead zirconate titanate ceramics

Abstract: In situ transmission electron microscopy study of the electric field-induced transformation of incommensurate modulations in a Sn-modified lead zirconate titanate ceramicThe ferroelectric-to-ferroelectic phase transformation between the high temperature (FE RH ) and the low temperature (FE RL ) rhomobohedral phases in lead based perovskite under the dc bias conditions was investigated. Dielectric measurements show that an external electric field stabilizes the FE RL phase and moves the phase transformation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Because of a short-range electrostatic interaction along the spontaneous polarization direction between Pb +2 cation and O -2 anions on adjacent cells, during cooling this interaction leads to a change in the spontaneous polarization direction from the thermal strain direction in the FE RH phase ([111] c in a pseudocubic lattice setting) to the oxygen octahedral rotation in the FE RL phase and results in a volume decrease upon phase transformation. 6 Therefore, the observed behavior could be attributed to a rapid release of this short-range electrostatic interaction in the lattice as the small volume of FE RL phase increases its volume on heating and suddenly transforms into a larger volume FE RH phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of a short-range electrostatic interaction along the spontaneous polarization direction between Pb +2 cation and O -2 anions on adjacent cells, during cooling this interaction leads to a change in the spontaneous polarization direction from the thermal strain direction in the FE RH phase ([111] c in a pseudocubic lattice setting) to the oxygen octahedral rotation in the FE RL phase and results in a volume decrease upon phase transformation. 6 Therefore, the observed behavior could be attributed to a rapid release of this short-range electrostatic interaction in the lattice as the small volume of FE RL phase increases its volume on heating and suddenly transforms into a larger volume FE RH phase.…”
Section: Resultsmentioning
confidence: 99%
“…The average of a positive CTE in the PE direction and a negative CTE in the PA direction leads to a near zero CTE value for the as-sintered samples. Because the spontaneous polarization in the FE RH is coupled to the thermal strain in the poled axis, 6 as temperature increases the spontaneous polarization progressively decreases and eventually diminishes at the Curie temperature. Concurrently, the strain decreases, resulting in a negative thermal expansion in this region.…”
Section: Resultsmentioning
confidence: 99%
“…Additional indications of cooperative tilt-polarization coupling are the fact that the application of an electric field in PZT modified with Sn and Nb enhances T T of few degrees. 75 and its prediction in BiFeO 3 from a first-principle simulation. 64 The coupling between FE and AFD modes has also been discussed in relation with the appearance of new Raman 76,77 and infra-red 21 modes below T T .…”
Section: Cooperative Tilt-polarization Couplingmentioning
confidence: 99%
“…As shown in Figure 4, the polarization hysteresis loop measurement up to 40 kV/cm in a circular disk bulk sample did not reveal any distortions that may suggest a phase change. Furthermore, there are experimental evidences that in a bulk ceramic with rhombohedral symmetry, electric fields stabilizes the FE RL phase (Yang et al, 2004a), whereas in BaTiO 3 single crystals, the ferroelectric-to-ferroelectric phase transition is dictated by the direction of the electric field (Wada et al, 1999).…”
Section: Electric Field In Situ Tem Studymentioning
confidence: 99%
“…When electric fields are applied to a polycrystalline ceramic specimen with random oriented grains, either FE RH or FE RL phase could be favored. A previous study with X-ray diffraction indicated that near the FE RH / FE RL phase transition temperature, the application of an electrical field favors the FE RL phase and expands its stable region to a higher temperature in a bulk Snmodified lead zirconate titanate ceramic (Yang et al, 2004a). In this study, the FE RH $ FE RL phase transition triggered by temperature and electric field was investigated by electron diffraction in transmission electron microscopy (TEM) in thin foils of a Nb-doped lead zirconate titanate ceramic.…”
Section: Introductionmentioning
confidence: 98%